Study on the features of H2S adsorbed on the graphene surface by using first principles. (November 2015) - Zhang, Q.; Sun, Y.; Luo, Q.; Tang, B.; Wu, Z. H.; Qiu, Y.; Ran, Z. L.
Abstract : By using the first principles based on the density functional theory, the adsorption properties of hydrogen sulphide on the graphene surface are studied in this paper. The structures and the electronic properties are calculated by the generalised gradient approximation. The adsorption energies of hydrogen sulphide adsorbed on graphene surface at the B, T and H sites are determined as −0.356, −0.410 and −0.332 eV, respectively. The results show that hydrogen sulphide adsorbed at the T site is stable, while H site is the most unstable adsorption site owing to the maximum absorption energy. When hydrogen sulphide is adsorbed on graphene surface, the band gaps of B, T and H sites are respectively 3.749, 3.889 and 3.589 eV so that the graphene is no longer a kind of conductor compared with clean graphene.